Pelatihan Konsep Building Information Modelling (BIM) melalui Aplikasi AutoCAD dan SketchUp bagi Siswa Kompetensi Keahlian DPIB SMKN 8 Pontianak: The Training of Building Information Modeling (BIM) Concept through AutoCAD and SketchUp Applications for DPIB Expertise Competency Students of SMKN 8 Pontianak - Sasongko, Hartanto Wahyu; Purnama, Ihkwan Arief; Reski, Indah Anjar; Riyanti, Rika; Rabihati, Etty; Setiawan, Randy; Haffiyan, Qalby; Perangin Angin, Imanuel Kemenangenta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Rapid developments in the construction era are shown by using the latest technology to improve efficiency and effectiveness in project implementation. One of the technologies widely used by construction experts today is Building Information Modeling (BIM). Building Information Modeling (BIM) is a digital-based concept that integrates 3D modeling and stores important information in the design, construction, and maintenance processes. Given the high demand for workers who are competent in BIM, there is a necessity for coaching or training on BIM applications to ensure that the developed workforce can fulfill the job market requirements. The purpose of this Community Service was to train students of SMK N 8 Pontianak with a concentration of expertise in Building Information and Modeling Design so that these students can better understand the concept of BIM. This training used AutoCAD and SketchUp software as tools for basic levels from 2D to 3D. The training results indicated that 74.18% of students at SMKN 8 Pontianak comprehended the concept of BIM, which they were previously unaware of, compared to a 28.64% percentage prior to the training. In addition, the ability of SMKN 8 Pontianak students to apply AutoCAD and SketchUp software has increased, as evidenced by the results of the images before and after the training. These results are anticipated to empower SMKN 8 Pontianak students to utilize their skills proficiently in the job market.